The Long-Lost Bulbostylis tenella (Cyperaceae): Rediscovery and Taxonomic Update with Lectotypification - Maciel-Silva, Juliene De Fátima; Larridon, Isabel; Prata, Ana Paula Do Nascimento; Gil, André Dos Santos Bragança (Phytotaxa, 2026)
Bulbostylis tenella is a rare micro-endemic species, previously known only from the type collection. The last report of the species has appeared in the literature only through a nomenclatural combination published by C.B. Clarke in 1908, and the lack of available material led to it being overlooked in all subsequent studies. Here, we report the rediscovery of B. tenella, 117 years after its last citation in the literature, and provide a detailed description, lectotypification, conservation assessment, photographs, and a distribution map of the species.